Study of Stability Criteria of Numerical Solution of Ordinary and Partial Differential Equations Using Euler’s and Finite Difference Scheme (Journal of Partial Differential Equations, 2022)
In this paper we have discussed solution and stability analysis of ordinary and partial differential equation with boundary value problem. We investigated periodic stability in Euler’s scheme and also discussed PDEs by finite difference scheme. Numerical example has been discussed finding nature of stability. All given results are more accurate than existing methods.
Keywords: Stability; ordinary and partial differential equations; Eulers and finite difference scheme.